Anthropometric and Genetic Correlation of Hand Dimensions for Forensic Identification in a Pakistani Population - Sadaf Sajid, Muhammad Saeed, Nasir Abbas, Nida Yousaf, Mansoora Mirza, Khyzer Hayat Sukhera (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
In forensic identification, reliablepopulation-specific data on hand dimensions and their biological underpinnings remainscarce for Pakistani communities.